Mobilidade e direito à cidade: um estudo do impacto do Bilhete Único junto a usuários do metrô de São Paulo - Neves, Denise Porto (2013)
This research aims at reflecting on the impact of the use of BilheteÚnico (B.U.) on the users of public transportation, primarily the subway system in São Paulo.The topic relates to the understanding and analysis of the needs of public transportation users in the city, which has many problems regarding its spatial configuration, social inequalities, segregation, difficulties accessing the places built to the majority of the population.Particularly, those difficulties concern the mobility, mainly in relation to three core areas: the commute to work, to schools and to leisure places.São Paulo start-up and expansion processes took to the peripheries a large number of people and, together with them, the worsening of their life conditions, as regard poor housing, health, education and leisure conditions, as well as the lack of infrastructure. The city shows itself as unbalanced by revealing unequal income distribution. Considering that public transportation is a relevant factor to promote the access to the city and to the means needed to live, for instance, to work (essential to the struggle for survival), to education and leisure equipment, we can state the importance of a transportation policy that aims at contributing to reduce exclusionary and segregating mechanisms.The subway system (Metrô) has stood out among the means of transport used; therefore, it has become an important means to face the issues of mobility, mainly after the acceptance of Bilhete Único . The number of users, specially to metropolitan region residentes, has increased.The research selected an urban axis to analyse its application, the East-West line, red 3-line, since it receives the greatest flow of people. We started with bibliographic and documentary research, using secondary data from Metrô of São Paulo and qualitative procedure by the selecting intentional sample. Then, we had interviews with Bilhete Único users. The research field was held according to three main strategies: beside the self-service vending machines, with random users; in front of university UNINOVE Barra-Funda and at the front desk of SESC Itaquera. After the analysis of the collected data, we conclude that the promotion of BilheteÚnico was a relevant factor in the lives of the public transportation users and in the lives of those who live in regions that are distant from job, higher education and leisure park offer áreas. Thus, BilheteÚnico seemed to be decisive in relation to commute time reduction, trasport expenses saving and greater possibilities of leisure and free time